From Survey to Policy: Community Relations in Northern Ireland. (February 2014) - Devine, Paula; Robinson, Gillian
Public policy is expected to be both responsive to societal views and accountable to all citizens. As such, policy is informed, but not governed, by public opinion. Therefore, understanding the attitudes of the public is important, both to help shape and to evaluate policy priorities. In this way, surveys play a potentially important role in the policy making process. The aim of this paper is to explore the role of survey research in policy making in Northern Ireland, with particular reference to community relations (better known internationally as good relations). In a region which is emerging from 40 years of conflict, community relations is a key policy area. For more than 20 years, public attitudes to community relations have been recorded and monitored using two key surveys: the Northern Ireland Social Attitudes Survey (1989 to 1996) and the Northern Ireland Life and Times Survey (1998 to present). This paper will illustrate how these important time series datasets have been used to both inform and evaluate government policy in relation to community relations. By using four examples, we will highlight how these survey data have provided key government indicators of community relations, as well as how they have been used by other groups (such as NGOs) within policy consultation debates. Thus, the paper will provide a worked example of the integral, and bi-directional relationship between attitude measurement and policy making.